Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3390/ijms13044101
|View full text |Cite
|
Sign up to set email alerts
|

Subminimal Inhibitory Concentrations of the Disinfectant Benzalkonium Chloride Select for a Tolerant Subpopulation of Escherichia coli with Inheritable Characteristics

Abstract: Exposure of Escherichia coli to a subminimal inhibitory concentration (25% below MIC) of benzalkonium chloride (BC), an antimicrobial membrane-active agent commonly used in medical and food-processing environments, resulted in cell death and changes in cell morphology (filamentation). A small subpopulation (1–5% of the initial population) survived and regained similar morphology and growth rate as non-exposed cells. This subpopulation maintained tolerance to BC after serial transfers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 56 publications
5
31
0
Order By: Relevance
“…This result agrees with previous reports documenting the adaptive BAC insusceptibility in E. coli, where microarray analysis indicated the involvement of active efflux (43). However, in contrast to previous reports, significant upregulation of the AcrAB efflux system or the outer membrane protein TolC was not observed, and there was no significant increase in the transcription of stress response systems, such as those belonging to the SoxRS regulon, or the multiple antibiotic resistance operon MarA (43,50). An increase in the transcription of genes associated with the Mdt and Yhi efflux systems was observed, which could further explain the minor changes in BAC susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with previous reports documenting the adaptive BAC insusceptibility in E. coli, where microarray analysis indicated the involvement of active efflux (43). However, in contrast to previous reports, significant upregulation of the AcrAB efflux system or the outer membrane protein TolC was not observed, and there was no significant increase in the transcription of stress response systems, such as those belonging to the SoxRS regulon, or the multiple antibiotic resistance operon MarA (43,50). An increase in the transcription of genes associated with the Mdt and Yhi efflux systems was observed, which could further explain the minor changes in BAC susceptibility.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of biocides in antibiotic resistance has been explored in different studies specifically focused on particular situations of cross-resistance or induction of resistance (2,23,(36)(37)(38)(39). In this study, we went one step further and comprehensively analyzed the high diversity of effects exerted by several biocides and antibiotics on the most relevant enterobacterial pathogenic species, E. coli and K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…In a hospital setting, exposure of bacteria to residual concentrations of biocides could occur for example when residues of a compound are left on a surface after disinfection. Such exposure could potentially lead to development of increased resistance towards the biocide in use, as well as cross-resistance towards other antimicrobials, including antibiotics [11][12][13][14][15]. The exposure of bacteria to subinhibitory biocide concentrations could also induce other responses.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown how the transcriptome of various pathogens becomes altered after treatment with low concentrations of biocides [12,[23][24][25][26][27][28]. However, most of these studies investigated short-term response to sublethal or subinhibitory concentrations of biocides.…”
Section: Introductionmentioning
confidence: 99%